Khairi Waqf as an Instrument of Islamic Social Finance: Empowering Education and Healthcare in Rural Indonesia - Sari, Atika; Isnaini, Desi; Pramadeka, Katra (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study investigates the empowerment of khairi waqf in advancing educational and healthcare services within a rural Indonesian context, specifically in Sido Sari Village, Sukaraja District, Seluma Regency. Using a qualitative descriptive approach, data were collected through in-depth interviews, field observations, and document analysis involving nazirs, village officials, educators, healthcare workers, and beneficiaries. Findings reveal that khairi waqf played a pivotal role in establishing early childhood education (PAUD), madrasah, and community health services (posyandu), significantly improving access and equity for marginalized populations. The waqf initiatives were deeply embedded in local participation, reflecting the values of sadaqah jariyah, ta‘awun (mutual cooperation), and hifz al-nafs and hifz al-‘aql as core principles of maqashid shariah. However, the study also identifies challenges related to limited operational funding, untrained nazirs, policy fragmentation, and declining youth engagement in waqf literacy. These issues underscore the need for transitioning from static to productive waqf models, formalizing multi-level governance, and integrating waqf into local development and religious education frameworks. This research contributes to the discourse on Islamic social finance and rural development by offering a context-sensitive model of waqf empowerment that combines spiritual intent, professional governance, and grassroots synergy.